Prognostic role of the lymph node ratio in colorectal cancer: A retrospective study - ERGENÇ, MUHAMMER (My University, 2022)
Background: Studies have been conducted to investigate more practical and useful parameters in determining the prognosis of patients with colorectal cancer (CRC), and some suggest that the lymph node ratio (LNR) may be useful in doing so, especially in patients with inadequate lymph node dissection. Objectives: We aimed to evaluate the effect of LNR (number of metastatic lymph nodes/number of total lymph nodes excised) on disease‑free survival and overall survival rates in CRC. Design: A single‑center retrospective cohort study. Setting: Tertiary care hospital. Patients and Methods: The clinical and pathological features of the patients were analyzed by dividing them into groups according to tumor localization; tumor, node, metastasis staging; and LNR. The Kaplan–Meier method and the log‑rank test were used for survival analysis. Sample Size: A total of 479 patients with CRC who were operated on between September 1991 and December 2011 were included in this study. The LNR of 439 patients could be calculated, and analyses were according to these patient groups. Main Outcome Measures: The primary objective of this study was to determine the effect of LNR on disease‑free survival and overall survival in CRC. Results: A total of 121 right‑sided colon cancers, 202 left‑sided colon cancers, and 156 rectal cancers were analyzed. The age of the patients ranged from 20 to 93 years, and the mean age was 66.8 (13.5) years. The cumulative 5‑year survival rate was 48.5% in our patients with CRC. When analyzing the tumor, node, metastasis stages of the groups according to their LNRs, the results showed that as the rate of lymph node metastasis increases, so does the tumor stage parameter (P < 0.001). The overall survival and disease‑free survival rates significantly decreased as LNR increased (P < 0.001). Conclusion: This study showed that LNR correlates well with the disease‑free and overall survival rates. A higher LNR could indicate the aggressiveness of the tumor; therefore, LNR may be a predictor of the poor prognosis of CRC. Limitations: Some patients could not be followed‑up and we could not evaluate complications because not all patients had data on postoperative complications. As a result, our study results may have been affected. Conflict of Interest: The authors have no conflict of interest to declare.
Keywords: Colorectal cancer; lymph node ratio; lymph node staging; metastatic tumor; prognostic factor; survival outcome